Приключения котенка с улицы Лизюкова - Злотников Виталий Маркович (Коллекция любимых сказок, 2017)
Экземпляры: (20230126) / Инвентарный номер: 41260 / Цена: 128.00 / Сис.шифр: 84(2Рос=411.2)6 / Авт.знак: З-68 / ГРНТИ: 17.82 / ББК: 84(2Рос=411.2)6